The Sustainable Development Program with the Neoliberal Approach: A Reflection on The UN Decade of Education for Sustainable Development - Zou, Qijia (European Journal of Sustainable Development, 2023)
In recent decades, addressing the environmental issues through deliberate educational interventions was optimistically seen by multiple actors, and has become a dominant discourse in current policy agendas. Since Education of Sustainable Development (ESD) is contextualized in the grand socio-political canvas, and certainly complicated in terms of its ways that came into existence and manner of expression. As we are half-way to approaching the education 2030 agenda, it’s time for us to take a step back and re-examine the ideological and political drivers. This is an important step to reflect on where the path we embark on is leading us to. This paper aims to uncover how the ESD was shaped by the logic of neoliberalism in the first place, and how this manifested in the contemporary sustainable development education program. Next, using a rhetorical analysis along with the Hyatt’s Critical Discourse Policy Analysis Frame into the textual construction of The Decade of Education for Sustainable Development (DESD) initiative document, this article considers about how neoliberal beliefs are reversing as reasonable grounds for mainstream discourse of ESD. Ultimately, the paper argues neoliberalism has been embedded, normalized and hence concealed in the discourses and practices of sustainable development, as exemplified by DESD initiative. Keywords: DESD; ESD; neoliberalism; sustainability citizenship